Cancer Pain Management in French-Speaking African Countries: Assessment of the Current Situation and Research Into Factors Limiting Treatment and Access to Analgesic Drugs - Hadjiat, Yacine; Perrot, Serge (Frontiers in Public Health, 2022)
Introduction There is a dearth of research on the incidence and treatment of cancer pain in Africa. Yet Africa, with other developing countries, accounts for more than half of all cancer diagnoses, and it is estimated that cancer incidence in Africa will double by 2030. Objectives This research protocol outlines an approach to investigate cancer pain in French-speaking African countries. The protocol intends to determine and describe the treatment and management of cancer pain in these countries. Barriers to treating cancer pain will be explored and the results will be collated to make a series of recommendations on policy positions, regulatory frameworks and protocols. Methods A mixed-methods, co-creation methodology has been selected to ensure the societal impact of the research outcomes. This research will use both qualitative and quantitative data collection methods and analyses. The research will begin with a review of the policies and legislation that exist in relation to cancer pain management and the use of analgesics, in each French-speaking African country. An Experts Steering Committee will then be created to provide guidance on the protocol and research design and access to participants, as well as to execute on the administration of surveys to local structures and international experts. A series of semi-structured, qualitative interviews with experts and clinicians in the field of screening and management of cancer pain and access to treatment will follow. Purposive and snowball sampling will be used to select the respondent experts. The semi-structured interviews will be conducted to determine the main trends and barriers to the treatment of cancer pain in French-speaking African countries. From this qualitative research, two surveys will be developed and then administered: one to validate the policy and regulatory context, and the other to determine experts and healthcare professionals experience and perceptions of cancer pain. Results/Conclusions The results will be analyzed using quantitative and qualitative methods to determine themes and perceptions of cancer pain and treatment, from the policy level to the healthcare professional level. Evaluation of the results will lead to recommendations for a comprehensive framework for cancer pain treatment in French-speaking Africa.